Forensic context of deception and lies: the intellectual aspect of tactics - Krasikau, Uladimir S. (Journal of the Belarusian State University. Law, 2021)
The article examines the problems of the criminalistic context of the concepts of deception and lies in law enforcement, their perception in the field of criminalistics, criminal procedure and operational investigative activities, which solve the problems of detecting, suppressing and investigating crimes. The main concepts that form ideas about the permissibility (inadmissibility) of deception and lies in forensic tactics are studied. The point of view on the prospects of studying the problem under study through the intellectual aspect of interaction of subjects involved in criminal procedure or operational search relations is proposed.
Keywords: deception; lies; conflict; forensic conflictology; interaction in law enforcement; intellectual aspect of forensic tactics; forensic context